1991
DOI: 10.1128/jb.173.15.4717-4724.1991
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the Pseudomonas putida regulatory protein CatR: transcriptional studies and determination of the CatR DNA-binding site by hydroxyl-radical footprinting

Abstract: CatR, a LysR family protein, positively regulates the Pseudomonas putida catBC operon, which is required for growth on benzoate as a sole carbon source. Transcriptional studies show that the catR and catBC promoters are divergent and overlapping by 2 bp. A I8-galactosidase promoter probe vector was constructed to analyze expression from the catR and catBC promoters under induced and uninduced conditions. As predicted, the catBC promoter is expressed only under induced conditions, while the catR promoter is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 43 publications
(43 reference statements)
2
62
0
Order By: Relevance
“…In both cases, the promoter fragments were inserted downstream of the rrnB T 1 T 2 transcription terminator in plasmid pTT3 to generate pTT3flrA and pTT3flaA, respectively. Then, the terminator-promoter fragment was inserted upstream of a promoterless lacZ gene in plasmid pKRZ1 (44) to generate pFlrA-LacZ and pFlaA-LacZ. To construct an rpoN-lacZ promoter fusion, we first constructed plasmid pLacZ by ligating a 4.4-kb BamHI-PstI fragment containing the lacZ gene from pKRZ1 to a 3.2-kb BamHI-PstI fragment from pBR322.…”
Section: Methodsmentioning
confidence: 99%
“…In both cases, the promoter fragments were inserted downstream of the rrnB T 1 T 2 transcription terminator in plasmid pTT3 to generate pTT3flrA and pTT3flaA, respectively. Then, the terminator-promoter fragment was inserted upstream of a promoterless lacZ gene in plasmid pKRZ1 (44) to generate pFlrA-LacZ and pFlaA-LacZ. To construct an rpoN-lacZ promoter fusion, we first constructed plasmid pLacZ by ligating a 4.4-kb BamHI-PstI fragment containing the lacZ gene from pKRZ1 to a 3.2-kb BamHI-PstI fragment from pBR322.…”
Section: Methodsmentioning
confidence: 99%
“…The role of the RBS and ABS is not completely clarified. Although ClcR and CbnR contacted both the RBS and ABS in the absence of inducer, CatR did not (215,216). It was concluded that the regulatory proteins have a higher binding affinity to the RBS than to the ABS, since a fragment with only the ABS is not bound by ClcR or CatR (139,181).…”
Section: Mechanisms Of Activationmentioning
confidence: 99%
“…The presence of cis,cis-muconate decreases the affinity of the BenM protein for benzoate (31). All LTTRs repress their own expression, and both autorepression and activation of the catabolic operon promoter are exerted from the same binding site, which is called the regulator or repressor binding site (RBS) (20,216,227). Autorepression was not influenced by the presence of an inducer in the case of BenM (20), but expression of the clcR and tcbR promoters was slightly enhanced in the presence of an inducer (33,263).…”
Section: Lysr Family Of Transcriptional Regulators Catabolic Operons mentioning
confidence: 99%
“…4, the DNase I-protected regions of the catBC promoter have been functionally divided into the repression binding site (RBS) and activation binding site (ABS). In the catR-BC promoter region, the RBS and ABS are implicated in the strong binding and autorepression of CatR on the catR promoter (13) and in the activation of the catBC promoter (11), respectively. In the clcR-ABD promoter region, the DNase I-protected sequences can be divided into two regions with sequence identities at 12 of 26 and 13 of 27 positions compared with the catR-BC RBS and ABS, respectively.…”
mentioning
confidence: 99%